2004
DOI: 10.1128/jvi.78.19.10291-10302.2004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ubiquitination and Other Covariant Phenotypes Attributed to a Strain- and Temperature-Dependent Defect of Reovirus Core Protein μ2

Abstract: Reovirus replication and assembly are thought to occur within cytoplasmic inclusion bodies, which we call viral factories. A strain-dependent difference in the morphology of these structures reflects more effective microtubule association by the 2 core proteins of some viral strains, which form filamentous factories, than by those of others, which form globular factories. For this report, we identified and characterized another strain-dependent attribute of the factories, namely, the extent to which they coloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Amino acid 208 in the 2 protein determines several strain-specific differences in 2 function (7,11,12). To determine whether this amino acid is also a determinant of 2 localization to nuclear speckles, AD-293 cells were infected with either the parental reovirus strains T1L or T3D or recombinant mutant viruses and then immunostained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid 208 in the 2 protein determines several strain-specific differences in 2 function (7,11,12). To determine whether this amino acid is also a determinant of 2 localization to nuclear speckles, AD-293 cells were infected with either the parental reovirus strains T1L or T3D or recombinant mutant viruses and then immunostained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MRV stocks (T1L, T2J, and T3D C ) were obtained from Max Nibert (Harvard Medical School, Boston, MA). The superscript C in T3D C is used to differentiate the T3D strain used in this study from a T3D strain (T3D N ) that has previously been shown to differ in M1 gene sequence, factory morphology, and 2 ubiquitination phenotype (37,43). Purified virions were prepared as described previously (12) and stored in virion buffer (150 mM NaCl, 10 mM Tris [pH 7.4], 10 mM MgCl 2 ) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study suggested that the T3 2 protein is subject to temperature-dependent misfolding (28), which led us to consider whether straindependent differences in viral replication efficiency in MDCK cells might be influenced by the temperature of infection. To test this hypothesis, viral titers were monitored in MDCK cells (Fig.…”
Section: Ultrastructural Analysis Of Viral Inclusions In Mdck Cellsmentioning
confidence: 99%